(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The article presents the study results of the development of functional pasta products through the enrichment of receipts with flaxseed meal and rosehip powder. The relevance of this work is determined by the need to expand the range of healthy food products on the Ukrainian market and to address the problem of the low nutritional value of pasta made mainly from soft wheat. The purpose of the research is development and scientifically substantiation of optimal pasta receipt with increased content of biologically active substances. During the experiment, control and three experimental pasta samples were produced, with a total content of 10% plant additives but with different ratios of flaxseed meal and rosehip powder. The comprehensive analysis of the organoleptic and cooking properties of the obtained samples was conducted. It was established that the incorporation of these additives positively affected on the nutritional value of the product by enriching it with dietary fiber, protein, omega-3 fatty acids, and vitamin C. On the base of the research results, the optimal receipt contained 5% flaxseed meal and 5% rosehip powder. This sample demonstrated the best balance between organoleptic characteristics (pleasant taste with a slight sourness, uniform reddish tint), cooking properties (shape retention rate after cooking of 94.4%), and nutritional value. Laboratory analysis confirmes that the developed product contains 10.73% protein, 6.1% dietary fiber, and 32.5mg/100g of vitamin C, it allows its classification as a functional food product. The proposed technology is promising for implementation in food industry enterprises for import substitution purposes and to meet the growing consumer demand for healthy food.